The impact of innovation on the structure of the assets of the enterprises - Humeniuk, Mariana; SHELENKO, Diana; Kovalchuk, Natalia; Balaniuk, Ivan (My University, 2022)
The article evaluates the impact of the intensity of innovation of the enterprise on the structure of its assets. The importance of optimizing the structure of assets to ensure the efficient operation of the enterprise is substantiated and the optimal structure of the company's assets is determined in terms of minimizing the duration of the operating cycle. It has been established that the process of optimizing the structure of enterprise assets in order to ensure the efficiency of its operation should be considered through the prism of comprehensive optimization of all components. The study of enterprises by the method of alternative valuations gave grounds to determine the ratio between non-current and current assets of 80:20, which may be optimal provided that automated and high-tech production. The sequence of stages of the asset structure optimization model has been proposed and described, the mechanism of determining the optimal structure at each of the stages is outlined, the expediency of practical application of the model is proved.
Keywords: innovative activity; assets; optimal structure; operating cycle